2009
DOI: 10.1136/gut.2008.174615
|View full text |Cite
|
Sign up to set email alerts
|

Molecular adsorbent recirculating system is ineffective in the management of type 1 hepatorenal syndrome in patients with cirrhosis with ascites who have failed vasoconstrictor treatment

Abstract: In patients with cirrhosis, refractory ascites and type 1 HRS not responding to vasoconstrictor treatment, MARS is ineffective in improving systemic haemodynamics and renal function despite reduction in NO levels, suggesting that vasodilatation in advanced cirrhosis is not due to excess systemic vasodilators alone. Transient reduction in serum creatinine indicates direct removal by MARS, and may not represent improved renal function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
40
0
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(41 citation statements)
references
References 54 publications
0
40
0
1
Order By: Relevance
“…However, no large-scale trial has been carried out and more recent studies (6 patients) in patients with type I HRS not responding to vasoconstrictor therapy found no improvement following MARS therapy in terms of systemic hemodynamics. They and others concluded that this therapy may only be effective as a bridge to transplant [31,32]. Prometheus employs fractional plasma separation, and adsorption with hemodialysis could be utilized to treat liver failure patients who have a need for RRT; however, it has not yet been studied in this group of patients.…”
Section: Introductionmentioning
confidence: 99%
“…However, no large-scale trial has been carried out and more recent studies (6 patients) in patients with type I HRS not responding to vasoconstrictor therapy found no improvement following MARS therapy in terms of systemic hemodynamics. They and others concluded that this therapy may only be effective as a bridge to transplant [31,32]. Prometheus employs fractional plasma separation, and adsorption with hemodialysis could be utilized to treat liver failure patients who have a need for RRT; however, it has not yet been studied in this group of patients.…”
Section: Introductionmentioning
confidence: 99%
“…Artificial liver support therapies have been evaluated for the treatment of HRS; including molecular adsorbent recirculating system (MARS), Prometheus, single pass albumin dialysis (SPAD), and single pass albumin extended dialysis (SPAED) [33][34][35][36][37]. These extracorporeal systems provide combined hepatic and renal support by removing water-soluble and albumin-bound toxins resulting in improved serum bilirubin, creatinine, and other laboratory measurements.…”
Section: Norepinephrine Versus Terlipressinmentioning
confidence: 99%
“…These extracorporeal systems provide combined hepatic and renal support by removing water-soluble and albumin-bound toxins resulting in improved serum bilirubin, creatinine, and other laboratory measurements. Unfortunately, these artificial support systems do not provide sustained responses in kidney function after discontinuation and laboratory values commonly return to pretreatment levels after discontinuation [33]. In addition to the inability to produce meaningful outcomes, other challenges to artificial liver support systems include hypotension, blood loss each time the circuit is replaced, and the frequent need for anticoagulant administration into the extracorporeal circuit to prevent clotting of the circuit.…”
Section: Norepinephrine Versus Terlipressinmentioning
confidence: 99%
“…In a randomized study, Mitzner et al [83] showed that MARS was superior to CRRT in type 1 HRS patients in terms of patient survival, improved clinical and biochemical parameters were also found. A more recent study demonstrated that MARS was ineffective in improving systemic haemodynamics in six patients with type 1 HRS who failed vasoconstrictor treatment; only transient reduction in serum creatinine occurred [84]. Another study on 32 HRS-1 patients reported a rate of complete renal response of 28% (9/32) [85].…”
Section: Therapy Of Hrs: Dialysismentioning
confidence: 99%